Women's Agency as Reason for Life Threats Among the Pashtuns in Pakistan: Narratives of Women Fleeing Honor Killing and Masculine Domination. (March 2023) - Khan, Saeeda; Thambiah, Shanthi; Khoo, Ying Hooi
This article uses the narratives of survivors of honor killing to show that women's agency is the reason for life threats because it undermines masculine domination. The findings show that life threats are made against women engaging in behaviors not aligned to cultural norms as perceived by male members of their family, to escape shame and gossip, and it is a manifestation of men losing control over women. These survivors of honor-based violence have undermined masculine domination by acting in unanticipated ways and by fleeing to a shelter home in the face of overwhelming cultural sanctions and structural inequalities.